Family Upbringing of Personality in the Pedagogical Inheritance of A.S.Makarenko - Bekirova, Adile (Pedagogical Discourse, 2013)
In accordance with the theme of the article, the author concentrates her attention on consideration of problems of family upbringing. On the basis of analysis of pedagogical inheritance of А.S.Makarenko the essence and content which are constituents of family upbringing of personality of child are revealed in the article. The leading ideas of the conception of family upbringing of А.S.Makarenko are considered. Educating potential of family and possibility of its using in educator space of general school is described. On the basis of analysis of A.S. Makarenko’s views to family upbringing the subjects of training for parents for the use in the system of educating work at school and with the aim to increase pedagogical culture of parents is worked out, the recommendations for parents as for the questions of education of children in the family are offered.